2023
DOI: 10.1038/s41598-023-39532-5
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the COVID-19 pandemic as a natural experiment to assess changes in antibiotic use and antibiotic-resistant E. coli carriage in semi-rural Ecuador

Heather K. Amato,
Fernanda Loayza,
Liseth Salinas
et al.

Abstract: The coronavirus 2019 (COVID-19) pandemic has had significant impacts on health systems, population dynamics, public health awareness, and antibiotic stewardship, which could affect antibiotic resistant bacteria (ARB) emergence and transmission. In this study, we aimed to compare knowledge, attitudes, and practices (KAP) of antibiotic use and ARB carriage in Ecuadorian communities before versus after the COVID-19 pandemic began. We leveraged data collected for a repeated measures observational study of third-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…A recent global review and meta-analyses found a non-statistically significant increase for resistant Gram-negative bacteria since the start of the pandemic, although this was based on literature of hospitalized patients and mostly focused on healthcare-acquired resistance ( 34 ). In contrast, in Ecuador, a middle-income country that implemented strict policies to reduce COVID-19 transmission, the prevalence of third-generation cephalosporin-resistant E. coli in children from semi-rural communities decreased from 40% to 23% between 2018 and 2021 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent global review and meta-analyses found a non-statistically significant increase for resistant Gram-negative bacteria since the start of the pandemic, although this was based on literature of hospitalized patients and mostly focused on healthcare-acquired resistance ( 34 ). In contrast, in Ecuador, a middle-income country that implemented strict policies to reduce COVID-19 transmission, the prevalence of third-generation cephalosporin-resistant E. coli in children from semi-rural communities decreased from 40% to 23% between 2018 and 2021 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%